Comparison of Mechanical Impedance Methods for Vibration Simulation - Jeffrey A. Gatscher; Grzegorz Kawiecki (Shock and Vibration)
The work presented here explored the detrimental consequences that resulted when mechanical impedance effects were not considered in relating vibration test requirements with field measurements. The ways in which these effects can be considered were evaluated, and comparison of three impedance methods was accomplished based on a cumulative damage criterion. A test structure was used to simulate an equipment and support foundation system. Detailed finite element analysis was performed to aid in computation of cumulative damage totals. The results indicate that mechanical impedance methods can be effectively used to reproduce the field vibration environment in a laboratory test. The establishment of validated computer models, coupled with laboratory impedance measurements, can eliminate the overtesting problems inherent with constant motion, infinite impedance testing strategies.